The influence of application of problem base learning model with the assistance of media tracker on students' learning interest at SMAN Anyer - Saputro, Handoyo; Asfarina, Marini; Fitriani, Deti Ihsan; Badrujaman, Roni; Muawanah, Yuyum (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2022)
The population for this study were all participants in class X SMA in Anyer. The sample for this study were students of class X-IIS 2 at SMAN in Anyer who were selected using the incidental technique. Assessment of the increase in students' learning interest after the application of the problem base learning model assisted by media tracker in learning activities, is carried out through the provision of questionnaires. The data was obtained after the students answered the questionnaire. The results showed that the application of the problem-based learning model assisted by the media tracker can improve students' literacy skills, especially in terms of interpreting graphs that affect students' learning interests. This is because the application of the problem-based learning model in learning activities causes students to be involved in investigative activities which give them the advantage of acquiring scientific abilities, helping develop students' abilities to conduct experiments and to get used to using experimental facts in deciding solutions to everyday problems.